SBML: a user interface mark-up language based on interaction style. (2nd May 2008) - Gilroy, Stephen W.; Harrison, Michael D.
As developers target a more diverse range of devices, a one-size-fits-all approach to interaction design becomes harder to sustain. By utilising the notion of interaction styles, developers can create families of user interfaces that are better matched to the interactive capabilities of devices. Style-Based Mark-up Language (SBML) is a language that separates services from style-specific interaction, and allows devices to choose the style of interface that best suits their capability and operating context. This paper outlines the service architecture and language syntax of SBML, using an online banking example. It also explores alternative single-interaction-style approaches and notions of context.